Autocontrole: um estudo sobre o efeito da variação simultânea da magnitude e do atraso do reforço e da possibilidade de realização de atividades distrativas - Menezes, Mariana São Thiago Bezerra de (2007)
The present study was aimed at analyzing child self-control through the simultaneous variation of magnitude and delay of reinforcement, with and without the possibility of engaging in a distracting activity during the delay of reinforcement. The participants, 11 children between the ages of five to eleven, with and without a diagnosis of ADHD, were presented with a computer task in a concurrent-chain schedule. The consequence produced by the response in the first link initiated the second link, and a new response, on the same component selected previously, produced, in VI 15s, a new consequence and the beginning of the period of delay of reinforcement (FT) with or without the distracting activities. The third link begun right after the end of the period of delay. The participants were submitted to two baseline conditions: one to evaluate the control that the magnitude of reinforcement dimension exerted over the response; and another to evaluate the control exerted by the delay of reinforcement dimension. In the experimental condition, there was simultaneous variation of magnitude and delay of reinforcement, with or without the possibility of engaging in distracting activities during the delay of reinforcement period. This variation involved four phases: in one of the components the magnitude and delay of reinforcement period remained constant (10s and 1 token); and in the other component, both were gradually increased (30s and 5 tokens, Phase 1; 60s and 10 tokens, Phase 2; 1min 30s and 15 tokens, Phase 3; e 2 min and 20 tokens, Phase 4). After that, the participants were submitted to a new condition, similar to the previous one, but without the distracting activities. Such condition was introduced from Phase 4. If the child reached the ending criterion for the phase (answering in ten consecutive attempts on one same component), the program was ended; if not, the child would go back to a previous phase, and thus successively. In all conditions, at the end of the period of delay, the period of access to reinforcement became effective. Tokens, represented by green traces on the computer screen, were used as reinforcers. Tokens were earned on a CRF schedule, and exchanged for toys at the end of the session. At the beginning of each session, participants established a specific value to each of the objects used as potential reinforcers. The maximum value was of 250 tokens and, gradually, by 10s, this value diminished till a minimum of 10 tokens. The hypothesis was that such values could indicate the potential reinforcing value of each object, so that the most valued reinforcer had the highest price (250 tokens) and the least valued reinforcer had the lowest price (10 tokens). At the end of each session, the participant checked the number of tokens he got, on the computer screen, and exchanged them for items he could buy, according to the value the participant himself had stipulated. The results showed that, in the phase of magnitude baseline, in the majority of the attempts, the children answered on the component that produced high magnitude, but in the delay baseline, the majority answered on the component that produced greater delay of reinforcement. When there was simultaneous manipulation of those variables, the participants answered more frequently on the component that produced higher reinforcement magnitude, in spite of greater delay of reinforcement, even with the gradual increase of the delay through the phases, up to 2 min. Results are discussed in relation to the number of responses emitted, in the presence and in the absence of such activities, and their possible reinforcing value